IABSE Symposium, Kolkata 2013: Long Span Bridges and Roofs - Development, Design and Implementation 2013
DOI: 10.2749/222137813808627802
|View full text |Cite
|
Sign up to set email alerts
|

Traffic Actions for the Design of Roadway Bridges: A Comparison of International Codes

Abstract: <p>Highway Bridge Design Codes and Loads from AASHTO LRFD, EUROCODE and Egyptian Codes are considered. Comparisons of action effects due to Traffic Actions (Live Loads) only, and Traffic actions combined with Permanent actions ( Dead Loads) are carried out. Load combinations at ULS &amp; SLS are considered. It is noted that comparing Traffic actions alone, a large difference is observed between codes (about 40%). When combined with Permanent actions (assuming concrete bridges), this difference reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Traffic loads are represented in the majority of modern design codes by models based on realistic traffic data, which differ from site to site, and hence national codes also differ. Comparison of national bridge design codes was conducted by Matar et al [21] who concluded that AASHTO [18] codes in general give lower design effects compared to Eurocodes [2]. In Croatia, design codes PTP-5 [22], with first traffic load models for the design of new bridges, were introduced after the Second World War in 1949 based on the guidelines from 1933 [23].…”
Section: Traffic Load Models -Overviewmentioning
confidence: 99%
“…Traffic loads are represented in the majority of modern design codes by models based on realistic traffic data, which differ from site to site, and hence national codes also differ. Comparison of national bridge design codes was conducted by Matar et al [21] who concluded that AASHTO [18] codes in general give lower design effects compared to Eurocodes [2]. In Croatia, design codes PTP-5 [22], with first traffic load models for the design of new bridges, were introduced after the Second World War in 1949 based on the guidelines from 1933 [23].…”
Section: Traffic Load Models -Overviewmentioning
confidence: 99%